Various Techniques for Controlling Transmit Power in Cognitive Radio: A Survey - Devi, Sarika; Goel, AK; Sehgal, Nikita (International Journal of Computer Sciences and Engineering, 2025)
Cognitive radio has been recently proposed as a promising technology to improve the spectrum utilization efficiency by intelligently sensing and accessing some vacant bands of primary users (PU). After reviewing fundamental papers it is found that much work has been done in the field of spectrum sensing for cognitive radio and different types of spectrum sensing methods. Transmitted power of CUs causes interference to PU when it is beyond tolerance limit. Most of this area has been remained untouched. This paper focuses on the work done in controlling the transmit power. In this situation, an effective and appropriate power control method is necessary for cognitive users for achieving quality of service (QoS).